Sumner family papers - Sumner, Edwin V. (Edwin Vose), 1797-1863.; Sumner, Edwin Vose, 1835-1912.; Sumner, Samuel S. (Samuel Storrow), 1842-1937.
Correspondence, legal documents, reports, and photographs of Edwin V. Sumner and his sons, Edwin Vose Sumner and Samuel Storrow Sumner, all military officers. Includes material on Civil War battles in Antietam, Md., and Fredericksburg, Williamsburg, and northern Virginia. Documents Edwin V. Sumner's 1855 audience with Frederick William IV, King of Prussia; Sumner's disagreement with General William S. Harney; a military expedition against the Sioux in 1855; and the training of soldiers at Fort Reno in the Indian Territory (later El Reno, Okla.) in the 1880s.
Sumner (Summers) family.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Frederick William -- IV, -- King of Prussia, -- 1795-1861.; Harney, William S. -- 1800-1889.; Summers family; Sumner family; Antietam, Battle of, Md., 1862.; Dakota Indians; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; Indians of North America -- Wars -- 1815-1875.; Military training camps -- Oklahoma; El Reno (Okla.); United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Virginia -- History -- Civil War, 1861-1865.; Williamsburg (Va.) -- History -- Civil War, 1861-1865.